Microencapsulated essential oils influence the growth and foregut histomorphometry of Nile tilapia (Oreochromis niloticus) fingerlings - Roldan Juarez, Jesús (2026)
Essential oils supplementation has potential growth-promoting, antibacterial, and immunostimulatory effects for various fish species. Dietary supplementation with essential oils improves Nile tilapia's growth and intestinal morphology. The aim of the study was to assess the effect of supplementation with microencapsulated essential oils (MEOs) containing cinnamaldehyde (53.9 %), thymol (24.2 %), and carvacrol (18.7 %) in Nile tilapia fingerlings on growth parameters and foregut histomorphometry. Six thousand fishes with initial body weights and lengths of 1.20 ± 0.32 g and 2.03 ± 0.40 cm, respectively, were reared in two separate 60 m3 circular tanks (control and supplemented with 500 mg/kg of MEOs) at a 5 kg/m3 density. Growth parameters included weight and length. Ten foregut samples per tank were collected at 0-, 15- and 30-days post-treatment. The histological analysis involved the size of intestinal folds and the number of goblet cells. Our results showed that fingerling growth parameters such as final body weight and length increased by 16.9 % and 10.43 %, respectively, with MEOs supplementation compared to the control group. Furthermore, histomorphometry results showed that the supplementation of MEOs led to a significant increase in the growth of both the width and length of intestinal folds and the number of goblet cells (p < 0.05). In conclusion, the early supplementation with MEOs improved the number, length, and width of intestinal folds and increased the number of goblet cells, positively influencing intestinal morphology and health. Additionally, MEOs improved growth parameters in Nile tilapia at 30 days of supplementation.